Reducing the throughput time for patient flow in emergency department: simulation and modelling overview - Hamza, Nidal Abdelgadir Ahmed; Mazlina, Abdul Majid; Al-Bashiri, Hael (IOP Publishing, 2019)
Satisfaction of patient considered as a main issue of quality of service in the healthcare sector. Typically, this satisfaction depends on the services quality provided by hospitals. Emergency Department (ED), as a critical department in the hospital, has a complicated registration system that may lead to increase the patient throughput time. Thus, to minimize this growing in the throughput time, numerous simulation and modelling, in the literature, have been developed and introduced. However, the throughput time in ED still represent in issue need for improvement to increase the ED performance. Therefore, in this paper, the main objective is providing an overview related to the characteristics and significance of current simulation and model techniques. As a result, in the ED realistically, integrating Agent-Based Simulation (ABS), Desecrate Event Simulation (DES), and System Dynamic (SD) techniques has been preferred as the solution to modelling the patient flow in ED and in turn may lead to decrease the throughput time. The proactive and independent characteristics of aforementioned techniques can contribute to the good representation the patients flow and their throughput time in ED.